2021
DOI: 10.1007/s00170-021-08073-4
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of hardfacing remanufacturing for large-scale damaged grinding roller

Abstract: The present study is directed to the temperature and residual stresses elds in the hardfacing remanufacturing for a large-scale grinding roller with damage. For this purpose, a numerical procedure for the hardfacing process based on thermal cycle curve method was established, and the effectiveness of the proposed procedure was veri ed by the measurements of a multi-pass welding experiment with Vgroove butt joint. Considering the characteristics of the hardfacing process, a local model of bead-onplate welding w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, after the backup roll serves under high load for a period of time, the roll surface is prone to spalling, making it unable to work properly. For the backup roll, because of its high technical requirements and difficulties in fabricating, the hardfacing technique is currently used for the roll surface repair [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, after the backup roll serves under high load for a period of time, the roll surface is prone to spalling, making it unable to work properly. For the backup roll, because of its high technical requirements and difficulties in fabricating, the hardfacing technique is currently used for the roll surface repair [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The papers [11,12] present modeling of multi-layer hardfacing with distribution of temperature, deformation and residual stresses of dissimilar welded butt joints with code written in ANSYS APDL and taking into account heat inputs in each element. The papers [13,14] provide modeling of the restoration of hardalloy surfacing parts. The results of numerical simulation revealed the trend of change and distribution of temperature fields and residual stresses during surfacing, taking into account the thermal cycle curve and phase transition effects.…”
Section: Introductionmentioning
confidence: 99%
“…The Stellite 6 layer had the lowest wear resistance in the dry sand/rubber wheel test, and the Stellite 6 layer had the highest wear resistance in the erosive blasting test. A numerical procedure for the hardfacing process based on a thermal cycle curve method was established by Tian et al [ 11 ] to research the temperature and residual stress fields in the hardfacing remanufacturing for a large-scale grinding roller with damage. The numerical simulation results showed that with an increase in surface layers, the heat-affected zone of the grinding roller gradually expands, and the maximum tensile stress always appears at the position near the weld toe, which is prone to fatigue failure or interface peeling due to stress concentration.…”
Section: Introductionmentioning
confidence: 99%